The Use of Audio Podcast for Teaching Listening Comprehension - Alfian, Alfian; Lio, Asrun; Sidu Marafat, La Ode (Halu Oleo University, 2019)
Podcast is created by combining of the word â€œiPodâ€ and â€œbroadcastâ€ and it produces audio and video files episodically that can be downloaded and listened by personal computer, tablet, smart phone, or another audio/video divice and listeners can listen and learn all interesting materials that they need. This research aimed to introduce audio podcast as a portable media for teaching listening. This media could be suggested to change conventional method in teaching listening. This research conducted at SMAN 1 Tanggetada in academic year 2016/2017. The type of this research was mix method and its design was quasi experimental design using pre-posttest. The group was divided into experimental and control groups. Experimental group was taught by audio podcast while control group was taught using conventional tool. The researcher analyzed the result of within and between groups using T-test while studentsâ€™ motivation was described by using interviews. The findings of the study showed that the use of podcast in listening was an effective media for teaching listening comprehension. The result of the interview indicated that most of the students are interested in audio podcast media. The media can motivate the students in listening as they can listen as many as possible at anytime and anywhere.